A new species of Ombrophytum (Balanophoraceae) from Chile, with notes on subterranean organs and vegetative reproduction in the family - Kuijt, Job; Delprete, Piero G. (Phytotaxa, 2019)
The Chilean desert specimens of Ombrophytum (Balanophoraceae) reported in the literature as O. subterraneum (Asplund) Hansen differ structurally in several respects from that species, which was described from moist tropical forest in Bolivia. Therefore the Chilean specimens are treated as a narrowly endemic, separate species, Ombrophytum chilensis Kuijt & Delprete, on the basis of the type specimen and published photographs. Discussions on morphology, distribution and conservation status are provided for this species. Critical comments on the underground organs and reproduction in Neotropical Balanophoraceae are also presented.